Human epidermal keratinocytes and human dermal fibroblasts interactions seeded on gelatin hydrogel for future application in skin in vitro 3-dimensional model - Tahri, Safa; Maarof, Manira; Masri, Syafira; Che Man, Rohaina; Masmoudi, Hatem; Fauzi, Mh Busra (Frontiers in Bioengineering and Biotechnology, 2023)
Plenty of biomaterials have been studied for their application in skin tissue engineering. Currently, gelatin-hydrogel is used to support three-dimensional (3D) skin in vitro models. However, mimicking the human body conditions and properties remains a challenge and gelatin-hydrogels have low mechanical properties and undergo rapid degradation rendering them not suitable for 3D in vitro cell culture. Nevertheless, changing the concentration of hydrogels could overcome this issue. Thus, we aim to investigate the potential of gelatin hydrogel with different concentrations crosslinked with genipin to promote human epidermal keratinocytes and human dermal fibroblasts culture to develop a 3D-in vitro skin model replacing animal models. Briefly, the composite gelatin-hydrogels were fabricated using different concentrations as follows 3% - 5% -8% and 10% crosslinked with 0,1% genipin or non-crosslinked. Both physical and chemical properties were evaluated. The crosslinked scaffolds showed better properties, including porosity and hydrophilicity, and genipin was found to enhance the physical properties. Furthermore, no alteration was prominent in both formulations of CL_GEL 5% and CL_GEL8% after genipin modification. The biocompatibility assays showed that all groups promoted cell attachment, cell viability, and cell migration except for the CL_GEL10% group. The CL_GEL5% and CL_GEL8% groups were selected to develop a bi-layer 3D-in vitro skin model. The immunohistochemistry (IHC) and hematoxylin and eosin staining (H&E) were performed on day 7, 14, and 21 to evaluate the reepithelization of the skin constructs. However, despite satisfactory biocompatibility properties, neither of the selected formulations, CL_GEL 5% and CL_GEL 8%, proved adequate for creating a bi-layer 3D in-vitro skin model. While this study provides valuable insights into the potential of gelatin hydrogels, further research is needed to address the challenges associated with their use in developing 3D skin models for testing and biomedical applications.